An exclusion map for Von Recklinghausen neurofibromatosis. - Sarfarazi, M (1987)
By using all the genetic linkage data available between Von Recklinghausen neurofibromatosis (VRNF) and various loci on the autosomes, a graphical display of all the non-excluded areas is presented. The probability of VRNF being on any of the 22 autosomes is also shown. The exclusion map presented is for 90 markers that have been localised relatively accurately. Data are also presented for a further 24 markers that have not yet been adequately localised. This exclusion map shows that most of the genome has been excluded as a likely location of any locus responsible for this disorder in the majority of families. Chromosomes 5, 10, 17, and 18 remain largely unexcluded. Concentration on these parts of the genome should help in the identification of the site of the VRNF gene.